53 Timing of Cardiac Rhythm Management Device Complications: Is Day Case Implantation Safe?. (3rd June 2016) - Nelson, Katharine; Welsh, Sarah; Batty, Jonathon; Lord, Stephen
Abstract : Introduction: Cardiac rhythm management (CRM) device implantation is a common medical procedure, considered to be safe in the majority of patients. Potential complications include pneumothorax, lead displacement, haematoma, infection and other wound problems. Whilst traditionally involving an overnight stay, some centres offer day-case procedures to selected patients. We sought to determine the time from implantation to detection of device-related complications, and thereby infer the safety of day-case implantation. Methods: A prospective database of all patients receiving a new CRM device, system replacement or upgrade over a 1 year period was maintained and screened for complications. Where identified, all medical, nursing and pacing notes were reviewed in order to determine first possible identification of a device-related complication; by symptoms, nursing observations or clinical investigations. Complications presenting less than 4 h post procedure were assumed to have prevented potential same day discharge. Pneumothoraces, pericardial effusions and wound problems were considered significant if they were actively managed. Lead displacements were considered significant if the patient experienced symptoms, loss of pacing function if pacing dependent, or a defibrillator discharge. Same-day discharge was considered to be non-inferior to routine discharge if no significant complication of pacing presented between 4 h and the time of routine discharge. Results: 109 complications occurred in 104 patients out of 1419 undergoing device implantation between October 2013 and September 2014. Complication rates according to device are detailed in Table 1 . 61 of 104 (58.7%) patients would not have been triaged to day case implantation due to an urgent device indication and/ or scheduled upgrade or system replacement. 6 (5.5%) complications presented before 4 h and so would have prevented early discharge. 22 presented after discharge the following day, our usual standard of care. 20 complications (5 pneumothoraces, 15 lead displacements) presented between 4 h and the time of discharge. One pneumothorax was managed with a chest drain having been identified on routine chest X-ray without prior symptoms or signs. Of 15 patients with lead displacement 4 (26.7%) experienced symptoms of twitch or palpitations, the remainder being identified on routine device interrogation the following day. 13 leads were repositioned or replaced and 2 were deactivated. There were no bradyarrhythmias, loss of pacing function when pacing-dependent or inappropriate defibrillator shocks. The were no device-related deaths or complications requiring ITU level care. Conclusion: Same day discharge appears safe in an unselected population of patients undergoing elective primary implantation of a CRM device at a high-volume cardiothoracic unit. Procedural difficulties, symptoms or signs suggestive of a potential complication should prompt further evaluation, and all patients should undergo device interrogation and chest radiography prior to discharge.